2x+66=5x+9

Simple and best practice solution for 2x+66=5x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+66=5x+9 equation:


Simplifying
2x + 66 = 5x + 9

Reorder the terms:
66 + 2x = 5x + 9

Reorder the terms:
66 + 2x = 9 + 5x

Solving
66 + 2x = 9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
66 + 2x + -5x = 9 + 5x + -5x

Combine like terms: 2x + -5x = -3x
66 + -3x = 9 + 5x + -5x

Combine like terms: 5x + -5x = 0
66 + -3x = 9 + 0
66 + -3x = 9

Add '-66' to each side of the equation.
66 + -66 + -3x = 9 + -66

Combine like terms: 66 + -66 = 0
0 + -3x = 9 + -66
-3x = 9 + -66

Combine like terms: 9 + -66 = -57
-3x = -57

Divide each side by '-3'.
x = 19

Simplifying
x = 19

See similar equations:

| (x+2)*(5-3x)= | | C^2-15c-54=0 | | 4(x+6)-x(x+6)=0 | | lg(2x)=4.5 | | 4(n-3)-3n=1+2 | | cos^2x+5cosx=1 | | 15x-17=22 | | 10+7f=8f | | 2x+18=-3y | | 3*(5*x-7)+2*(2*x+17)=5*(3*x-4)+37 | | (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 |

Equations solver categories